2016
DOI: 10.24953/turkjped.2016.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Seizures and diagnostic difficulties in hyperinsulinism-hyperammonemia syndrome

Abstract: Hyperinsulinism/hyperammonemia (HI/HA) syndrome is a rare disorder presented with recurrent hypoglycemia and elevated serum ammonia, which may lead to development delays, permanent neurologic damages, if it remains underdiagnosed. It is caused by activating mutations in the GLUD1 gene which encodes the intra-mitochondrial enzyme glutamate dehydrogenase (GDH).HI/HA syndrome is considered the second most common form of hyperinsulinism (HI), and usually associated with epileptic seizures, mental retardation and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…It is also interesting to outline that almost half of the proteins that are differentially expressed in EPM1‐derived organoids and enriched in radial glial cells are involved in different types of human epilepsies. For instance, Collagen COL11A1 mutated in the Stickler syndrome, caused by mutations in COL2A1 or COL11A1, is associated with epileptic phenotypes (Savasta et al , ; Zhou et al , ); IFITM3 (interferon‐induced transmembrane protein 3) has been identified among genes that are target of epilepsy‐associated miRNA in animal models and human tissues (Cava et al , ); heterozygous mutation in GLUD1 gene has been reported in patients affected by hyperinsulinism, commonly associated with epileptic seizures (Aka et al , ); RRAS (Guo et al , ) and MGST1 (Shang et al , ; Ercegovac et al , ) are associated with epilepsy risk.…”
Section: Discussionmentioning
confidence: 99%
“…It is also interesting to outline that almost half of the proteins that are differentially expressed in EPM1‐derived organoids and enriched in radial glial cells are involved in different types of human epilepsies. For instance, Collagen COL11A1 mutated in the Stickler syndrome, caused by mutations in COL2A1 or COL11A1, is associated with epileptic phenotypes (Savasta et al , ; Zhou et al , ); IFITM3 (interferon‐induced transmembrane protein 3) has been identified among genes that are target of epilepsy‐associated miRNA in animal models and human tissues (Cava et al , ); heterozygous mutation in GLUD1 gene has been reported in patients affected by hyperinsulinism, commonly associated with epileptic seizures (Aka et al , ); RRAS (Guo et al , ) and MGST1 (Shang et al , ; Ercegovac et al , ) are associated with epilepsy risk.…”
Section: Discussionmentioning
confidence: 99%
“… 7 This can lead to developmental delays and, if it remains undiagnosed, can lead to permanent neurologic damage. 7 , 8 Patients with HI/HA syndrome are usually responsive to diazoxide, which is an ATP-sensitive potassium (KATP) channel agonist. 1 , 5 , 9 , 10 There has been a report of variable phenotypes of this condition ranging from delayed presentation to spontaneous resolution of hypoglycemia but no report of T2DM developing in a patient with GLUD1 alteration.…”
Section: Discussionmentioning
confidence: 99%
“…It is caused due to an activating mutation in the GLUD1 gene, which is located on chromosome 10q23.3 (contains 13 exons) and encodes the intra-mitochondrial matrix enzyme glutamate dehydrogenase (GDH). Approximately 70% of these children have de novo mutation and 30% present with autosomal dominant inheritance ( 1 , 2 ).…”
Section: Introductionmentioning
confidence: 99%